MATERIALS MANAGEMENT TECHNOLOGY: AN APPLICATION IN CONSTRUCTION TECHNOLOGY - Narimah Kasim (Penerbit UTHM, 2011)
This book will assist readers to understand materials management processes and technologies in construction projects. It explained what is meant by materials management and discussed the materials management on construction projects. Also discussed were the processes and problems of materials management. The implementation of current technologies and potential to implement RFID in materials management practices were also discussed. It clearly identified that these are important for effectively managing materials management in the construction project in order to provide better handling of construction materials to provide an overall performance of construction projects in term of time, budget (cost) and quality. The application of ICT to support current practices of materials management in the construction site is considered improving for effective managing construction materials on site. In addition, the emerging technologies such as RFID are discovered to be a potential for improving materials management especially for tracking of materials.